Energy analysis of a collagen production process in Codland's Factory in Iceland - Árni Ingimarsson 1991- (2019)
The objective of this study is to look at waste heat utilization possibilities at a collagen production process based in Grindavík, called Codland. The utilization possibilities considered for the production process are mainly a small-scale electricity production with an ORC unit. Other possibilities that are considered are adding an additional heat exchanger to the process. Finally, the feasibility of relocating Codland towards a geothermal area is investigated with the emphasis on energy. It is estimated that Codland will produce 400 tons of dry gelatin from 4000 tons of fish skin on an annual basis. The production process is based on several food process methods such as extraction, purification, esterilisation and drying. The process requires steam which is produced on site with a 1 MW boiler which produces 800 kPa steam. An energy analysis is performed on the steam system based on data from Codland. The production of gelatin produces waste heat from the steam system which is analysed for each steam user and the condensate of the steam is estimated to be led to an accumulator. The condensate temperature is 113°C with a mass flow rate of 0.27 kg/s. An ORC model is set up in Engineering Equation Solver (EES) to investigate the feasibility of producing electricity from the waste heat. Six different working fluids are compared for the model and R1234yf was chosen. The maximum power output from the model was 9 kW with 9.8% thermal efficiency. The feasibility study shows that the setup of an ORC is not feasible, mainly due to the low mass flow rate of the steam. Sizing of a heat exchanger was investigated and concluded as 4800 cm2. A comparison of the current process and the process using geothermal energy was performed which supported the relocating of the production process. The relocating leads to a saving of 31.6 millions ISK in operation cost per year. Markmið þessa verkefnis er að skoða möguleika á varmaendurvinnslu hjá collagen framleiðslufyrirtækinu Codland í Grindvík. Varmaendurvinnslu möguleikarnir sem ...